(untitled) (International Journal of Statistics in Medical Research, 2016)
Summary: Esophageal cancer is one of the main health issues in Mizoram. The risk factors of the disease are related to consumption of alcohol. There have not been any epidemiological studies on this subject in the state. The aim of the study is to assess the relationship between esophageal cancer and consumption of alcohol. Materials and Methods: A hospital based matched case-control study was conducted comprising of 138 cases with histologically confirmed diagnosis of esophageal cancer and 276 controls that were cancer and esophageal cancer disease free. Cases and controls matched by gender and age (± 5 years). Ratio of cases and controls were 1:2. A questionnaire was used to collect information on possible risk factors of esophageal cancer. The odds ratios (OR) and 95% confidence intervals (CI) for gastric cancer were calculated by a conditional logistic regression. Results: Cases had significantly lower education level. Most of the cases are from middle income class. After adjustment for consumption of betel quid, tobacco, smoking, body mass index (BMI), family history of cancer, education level and income level, higher risk of esophageal cancer was found for those who have the habit of consuming alcohol in the morning. After controlling for consumption of betel quid, tobacco, smoking, body mass index (BMI), family history of cancer, education level, income level, dietary habits, physical activity, consumption of Zu(locally brewed alcohol) and both Zu(locally brewed alcohol) and commercial alcohol(rum, whisky, vodka and beer, etc) are also associated with higher risk of esophageal cancer (O.R = 9.820, 95% CI = 2.029-47.523).